2019
DOI: 10.1021/jacs.8b13280
|View full text |Cite
|
Sign up to set email alerts
|

KLi(HC3N3O3)·2H2O: Solvent-drop Grinding Method toward the Hydro-isocyanurate Nonlinear Optical Crystal

Abstract: A novel mixed alkali hydro-isocyanurate, KLi­(HC3N3O3)·2H2O was first prepared in AOH-BOH-H3C3N3O3 (A/B = Li/Na/K/Rb/Cs) system via a solvent-drop grinding method. KLi­(HC3N3O3)·2H2O shows a large second harmonic generation response (5.3 × KH2PO4) with an ultraviolet cutoff edge of 237 nm. More importantly, the bulk single crystal can be readily grown through water solution technique. Characterization of these crystals indicates that KLi­(HC3N3O3)·2H2O has a high laser damage threshold (LDT) (4.76 GW/cm2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
173
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(190 citation statements)
references
References 57 publications
7
173
0
Order By: Relevance
“…To nd a KBBF replacement, many new NLO crystals have been developed continuously, but have so far been unable to achieve desired NLO properties. [7][8][9][10] Recently, it was shown that uorooxoborates and uorophosphates with mixed O/F anionic groups might be recognized as new sources for discovering DUV NLO materials. For example, Pan's group proposed that the [BO x F 4Àx ] (x ¼ 1, 2, 3) tetrahedra are good units to balance the multiple criteria of DUV NLO materials.…”
mentioning
confidence: 99%
“…To nd a KBBF replacement, many new NLO crystals have been developed continuously, but have so far been unable to achieve desired NLO properties. [7][8][9][10] Recently, it was shown that uorooxoborates and uorophosphates with mixed O/F anionic groups might be recognized as new sources for discovering DUV NLO materials. For example, Pan's group proposed that the [BO x F 4Àx ] (x ¼ 1, 2, 3) tetrahedra are good units to balance the multiple criteria of DUV NLO materials.…”
mentioning
confidence: 99%
“…According to the UV/Vis‐IR reflectance spectra (Figure a), 1 has a high transmittance (80 %) in the wavelength above 290 nm and a wide transparency window covering from the near IR to UV spectral range. The UV absorption edge of 1 is 227 nm, corresponding to the band gap of 5.46 eV, which is comparable to those of Ba 3 (C 3 N 3 O 3 ) 2 (5.14 eV), KLHCY (5.23 eV), K 2 (HC 3 N 3 O 3 ) (4.95 eV),[18b] Ba 2 Mg(C 3 N 3 O 3 ) 2 (5.20 eV), and K 6 Cd 3 (C 3 N 3 O 3 ) 4 (5.23 eV) …”
Section: Resultsmentioning
confidence: 61%
“…1 is a PM material according to the Kurtz–Perry rule . Because the signal intensity is proportional to the squares of the effective SHG coefficient, the SHG coefficient of 1 is almost two thirds times that of KDP, much smaller than that of KLHCY (5.3 × KDP) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the anion framework, oxygen‐containing tetrahedra, such as SiO 4 , PO 4 , and BO 4 groups, are usually excluded from birefringent units because they make little contribution to the birefringence. While triangle or planar structure groups with π‐conjugation are beneficial for large birefringence, including BO 3 , NO 3 , CO 3 and C 3 N 3 O 3 . Of these, the BO 3 unit is considered as an excellent birefringent functional unit.…”
Section: Figurementioning
confidence: 99%